Dissolved and suspended particulate metals in Setiu River Basin, Terengganu, Malaysia - Koh, K. M.; Suratman, S.; Mohd Tahir, N. (Universiti Kebangsaan Malaysia, 2015)
Dissolved and suspended particulate metals (Al, Fe, Cd, Cu, Zn, Pb) in Setiu River basin, Terengganu which is situated at coastal area of southern South China Sea were investigated. The water samples were collected from nine stations from June 2007 to January 2008, in conjunction with the Southwest monsoon and Northeast monsoon. The average concentrations of dissolved Al, Fe, Cd, Cu, Zn and Pb were (μg L-1): 50±60, (2.0±3.4) ×102, 2.5±2.6, 3.0±1.4, 7.5±5.1 and 6.0±5.0, respectively. Meanwhile, the concentrations of suspended particulate metals were (μg g-1): (13±10)%, (10±13)%, 15±13, 65±94, (3.5±2.5) ×102 and (1.2±1.5) ×102, respectively. Seasonal variations of dissolved and suspended particulate metals were observed. The results were compared with selected Malaysian national rivers, world average and established guidelines. In addition, the enrichment of suspended particulate metals and the partitioning of metals between dissolved and suspended particulate phases were discussed.